Kesalahan Berbahasa pada Teks Anekdot Politik Lucu pada Website https://edukasi.okezone.com Edisi Januari 2025 - Haris Budisetiawan; Ezra Malvino Putra Alwi; Azi Aurahman Elegan; Muhammad Rolanda Hendrakusuma; Arshi Vinusia; Marta Alfiana Damayanti; Riri Kumala Sari; Samuel B.T. Simorangkir (BADAN PENERBIT STIEPARI PRESS, 2025)
Language assumes a fundamental role in human life and is essential for communication and survival. This research aims to explore and analyze the various types of phrases that are found in the online article entitled